Human airway epithelium controls Pseudomonas aeruginosa infection via inducible nitric oxide synthase - Grubwieser, Philipp; Böck, Nina; Soto, Erika Kvalem; Hilbe, Richard; Moser, Patrizia; Seifert, Markus; Dichtl, Stefanie; Govrins, Miriam Alisa; Posch, Wilfried; Sonnweber, Thomas; Nairz, Manfred; Theurl, Igor; et al. (Frontiers in Immunology, 2024)
IntroductionAirway epithelial cells play a central role in the innate immune response to invading bacteria, yet adequate human infection models are lacking.MethodsWe utilized mucociliary-differentiated human airway organoids with direct access to the apical side of epithelial cells to model the initial phase of Pseudomonas aeruginosa respiratory tract infection.ResultsImmunofluorescence of infected organoids revealed that Pseudomonas aeruginosa invades the epithelial barrier and subsequently proliferates within the epithelial space. RNA sequencing analysis demonstrated that Pseudomonas infection stimulated innate antimicrobial immune responses, but specifically enhanced the expression of genes of the nitric oxide metabolic pathway. We demonstrated that activation of inducible nitric oxide synthase (iNOS) in airway organoids exposed bacteria to nitrosative stress, effectively inhibiting intra-epithelial pathogen proliferation. Pharmacological inhibition of iNOS resulted in expansion of bacterial proliferation whereas a NO producing drug reduced bacterial numbers. iNOS expression was mainly localized to ciliated epithelial cells of infected airway organoids, which was confirmed in primary human lung tissue during Pseudomonas pneumonia.DiscussionOur findings highlight the critical role of epithelial-derived iNOS in host defence against Pseudomonas aeruginosa infection. Furthermore, we describe a human tissue model that accurately mimics the airway epithelium, providing a valuable framework for systemically studying host-pathogen interactions in respiratory infections.